Risk factors associated with tendon adhesions after hand tendon repair - Jia, Qiyu; Chen, Dongsheng; Guo, Jian; Luo, Xuefeng; Alimujiang, Abudusalamu; Zhang, Jun; Hu, Ningning; Liu, Yanshi; Xie, Zengru; Ma, Chuang (Frontiers in Surgery, 2023)
Background Tendon adhesions after hand tendon repair are one of the most difficult complications of hand surgery and can cause severe disability. This study aimed to assess the risk factors associated with tendon adhesions after hand tendon repair to provide a theoretical foundation for the early prevention of tendon adhesions in patients with tendon injuries. Moreover, this study intends to increase doctors' awareness of the issue and serves as a reference for developing new prevention and treatment strategies. Methods We retrospectively analyzed 1,031 hand trauma cases that underwent repair after finger tendon injury in our department between June 2009 and June 2019. Tendon adhesions, tendon injury zones, and other relevant information were collected, summarized, and analyzed. The significance of data was determined using a t-test or Pearson's chi-square test, and odds ratios (OR) were calculated using logistic regression tests to describe factors associated with post-tendon repair adhesions. Results A total of 1,031 patients were enrolled in this study. There were 817 males and 214 females with an average age of 34.98 (2–82) years. The injured side included 530 left and 501 right hands. Postoperative finger tendon adhesions occurred in 118 cases (11.45%), including 98 males and 20 females, 57 left and 61 right hands. The risk factors for the total sample in the descending order were degloving injury, no functional exercise, zone II flexor tendon injury, time from injury to surgery >12 h, combined vascular injury, and multiple tendon injuries. The flexor tendon sample shared the same risk factors as the total sample. Risk factors for the extensor tendon sample were degloving injury, no functional exercise. Conclusions Clinicians should pay close attention to patients with tendon trauma in hand having the following risk factors: degloving injury, zone II flexor tendon injury, lack of functional exercise, time from injury to surgery >12 h, combined vascular injury, and multiple tendon injuries. Due to the high risk of post-repair adhesions in patients with the conditions mentioned above, individualized treatment measures should be designed for the risk factors, and postoperative functional exercise of the hand is required.